Investigation of Anti-nociceptive Activity of Neem (Azadirachta indica) A. Juss on Acetic Acid Induced Writhing in Rats - Awad, Enas M.; Sirag, Nizar; Awadallah, Alla; Ahmed, Elhadi M. (Gezira Journal of Health Sciences, 2014)
Background : Plants represent the principal means of therapy in traditional medicine and the plant kingdom has long served as a prolific source of useful drugs. Objective: This study was undertaken to investigate the anti-nociceptive activity of Azadirachta indica A.juss leaf extract in experimental animals.   Methods : Three doses of methanolic extract of Azadirachta indica leaf (100, 200, and 400 mg/kg) were administered intraperitoneally (i.p.) to  investigate their potential antinociceptive activity using acetic acid induced writhing in rats compared to morphine and diclofenac sodium as standard drugs.   Results : The methanolic extract of indica at a dose of 400 mg/kg produced 72.01% protection against writhing induced by acetic acid. This result points to approximately equal protection exhibited by 25mg/kg diclofenac sodium. Co-administration of indica (400 mg/kg) and diclofenac (25 mg/kg) produced 100% protection as diclofenac sodium (50mg/kg) and morphine (2.5, 5 mg/kg). Conclusion and recommendation : On the basis of results obtained, the use of indica leaf extract as antinociceptive seems to be promising. Bioassay guided fractionation of the methanolic extract of indica leaf is recommended for safety and efficacious use. Further work on determination of active ingredient(s) and mechanism of action is also needed.